Etika Bisnis Pedagang Muslim Perspektif Islam - Bambang Priyowahono (Journal Khafi : Journal Of Islamic Studies, 2024)
This research aims to find out how Islamic business ethics are implemented in the Bujung Buring Mesuji market. The aim of this research is to find out how Islamic business ethics and how they are implemented in the Bujung Buring Mesuji market so that later it is hoped that the results of this research resume can be used as a summary framework or model for business actors in other markets. The research carried out is in the form of descriptive using observational studies and interviews. Results shows that the Muslim traders at the Bujung Buring Mesuji market who were used as informants have implemented the principles of Islamic business ethics including; provide good service, be honest and patient, be responsible, and set prices fairly. Traders also always obey the regulations made by the Bujung Buring market manager.